Klasterisasi Konsentrasi Keahlian Siswa SMK Berdasarkan Kurikulum Merdeka - Firman Sukmayadi; Alamsyah Firdaus; Christina Juliane (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The process of determining the concentration of expertise carried out at the YPC Tasikmalaya Vocational School has shortcomings such as making decisions based on the wishes of students without paying attention to academic grades at the previous level of education. So that there are some students who feel it is not right in choosing the concentration of expertise, resulting in a lack of competence possessed by students with the concentration of expertise selected. The choice of concentration of expertise is the right of every student, but if it is wrong it can cause a decrease in learning motivation and low learning achievement. This problem can be solved by using clustering method with K-Means algorithm. This study aims to classify students' interests in choosing a concentration of expertise at YPC Tasikmalaya Vocational School based on the Merdeka Curriculum. The results showed that the grouping of students' interests in choosing the concentration of expertise was formed into 4 clusters. The cluster with the most members is cluster 0, namely students who have an average score of 79 Mathematics, then Indonesian and English 83. Furthermore, the cluster with the least number of members is cluster 2, namely students who have an average score of 78 Mathematics and English, then Indonesian 79.